Analysis of a Statewide Maternal Transport System: A Four-Year Review [04N]. (May 2020) - Kogutt, Benjamin K.; Morris, Bernard D.; Applebaum, Jeremy; Hall, Valerie; Phillips, Michelle; Sheffield, Jeanne S.
Abstract : INTRODUCTION: Implementing levels of maternal care (LOMC) dictates that certain maternal conditions be centralized to risk-appropriate care centers. However, the feasibility of a LOMC system is dependent on the ability to transport risk appropriate patients in a timely manner. The objective of this study is to describe maternal transports via a robust, state-sponsored maternal transport system. METHODS: This is a retrospective cohort study of all maternal transports from Sept '15 through Jun '19 into the Johns Hopkins Medical system. Data were extracted from maternal transport logs and electronic medical records. RESULTS: Of 1, 392 maternal transports over the study period, 652 (47%) were for maternal indications. The majority of transports originated from Level I centers (37%). The median distance travelled per transport was 26 miles: 70% by ambulance and 21% by helicopter. 48% of transported mothers delivered during their admission at the receiving hospital. Average maternal age was 29 years, with 48% of mothers being white, 42% black. Average infant weight was 1926 grams, with a 66% NICU admission rate. 18% of transports were suspected preventable if antepartum care was transferred prior to the delivery episode with the most frequent indications for transport being hypertensive disease of pregnancy (34%), infection (8%) and placentation (6%). CONCLUSION: Maryland has had an established, regionalized maternal care system since the early-1990s, with clearly defined LOMC and a functioning transport network. Our findings demonstrate utilization patterns within such a program and describe key characteristics of transporting hospitals and patients. Further research is needed to determine the effectiveness of LOMC.